Antiarrhythmic medication for atrial fibrillation (AIM-AF) study: a physician survey of antiarrhythmic drug (AAD) treatment practices and guideline adherence in Europe. (14th October 2021) - Blomstrom-Lundqvist, C; Camm, A.J; Goette, A; Kowey, P.R; Merino, J.L; Piccini, J.P; Reiffel, J.A; Saksena, S; Boriani, G
Abstract: Background: The 2020 European Society of Cardiology (ESC) guidelines provide detailed recommendations for the management of patients with atrial fibrillation (AF). In symptomatic patients, AADs are advised for rhythm control. Purpose: This study was designed to investigate AAD treatment practices and adherence to guidelines in four European countries. Methods: An online survey (n=321) of cardiologists or cardiac electrophysiologists (CDs) and interventional electrophysiologists (EPs) was conducted in Germany (DE; n=83), Italy (IT; n=95), Sweden (SE; n=60) and the UK (n=83). Respondents were actively treating ≥10 patients with AF. Results: (1) The majority of physicians considered guidelines to be the most important non-patient factor influencing their AF management practices (pooled: 65%; range: 55–72%), with 96% (range: 89–100%) following ESC guidelines. Although amiodarone use was most frequent in heart failure with reduced left ventricular (LV) ejection fraction (pooled: 91%; range: 88–93%) where it is a recommended first-line option, non-adherent AAD selection was common. Amiodarone was frequently selected as a typical treatment choice for minimal/no structural heart disease (SHD) where it is not recommended for initial therapy; this was particularly common in the UK versus SE (Figure 1). Other deviations included use of class 1C drugs in those with coronary artery disease (CAD) (with the exception of SE; Figure 1) and other SHD, as well as use of sotalol in LV hypertrophy (pooled: 30%) and renal impairment (Figure 1). Furthermore, absence of inpatient initiation of sotalol was generally high, with the exception of SE (Figure 1). (2) Sotalol and dronedarone use in CAD varied between country (pooled: 28% [range: 16–41%] and pooled: 19% [range: 10–54%], respectively). (3) CDs and EPs used rhythm control as initial therapy in most patients with paroxysmal AF (PAF); however, other than SE, this was not the case for persistent AF (Figure 2). (4) AADs were preferred over ablation as initial therapy for individuals with infrequent, mildly symptomatic PAF (pooled: 61%), with the exception of SE (48%). Ablation was favoured for most patients with frequent, symptomatic PAF; however, in SE, AADs were preferred for infrequent, highly symptomatic PAF (53%) and frequent, symptomatic PAF (53%). (5) Rhythm control therapies were selected for asymptomatic or subclinical AF; AADs were used more often (average: 41% [range: 22–60%]; ablation was used less frequently (average: 11% [range: 2–18%]). Conclusion: Despite assertion that guidelines are the primary determinant for rhythm control treatment decisions, non-adherence was notable in European practice. While deviation may be reasonable in select individual patients, in general, non-adherence could compromise patient safety. As such, establishing the drivers of non-adherent practices is key, and education directed at clinicians to improve optimal and safe use of AADs is warranted in Europe. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Sanofi